Pengaruh Kepemimpinan dan Motivasi Terhadap Kinerja Pengurus pada Dewan Pengurus Cabang PKB Cilacap - Heni Setyaningsih; Hakim Hakim; Syafi’ah Syafi’ah (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to analyze the effect of Leadership and Motivation on the Performance of Board Members at the Branch Executive Board of Partai Kebangkitan Bangsa in Cilacap. Leadership and motivation are important factors in improving organizational effectiveness and productivity, particularly in political organizations that rely on the commitment and active participation of their board members. This research employed a quantitative approach using a survey method. Data were collected through the distribution of questionnaires to board members of the Branch Executive Board of PKB Cilacap. The data analysis techniques included validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²). The results show that partially, Leadership has a positive and significant effect on Board Members’ Performance, and Motivation also has a positive and significant effect on Board Members’ Performance. The coefficient of determination indicates that Leadership and Motivation explain 50.7% of the variation in Board Members’ Performance, while the remaining percentage is influenced by other variables not examined in this study.The study concludes that the better the quality of leadership and the higher the motivation of board members, the better their performance will be at the Branch Executive Board of PKB Cilacap. Therefore, improving leadership capacity and strengthening board members’ motivation should be prioritized to enhance organizational effectiveness.